Studies on Schismatoglottidae Araceae of Borneo I: A trio of new Schismatoglottis from Sarawak. - Boyce, P.C; Wong, Sin Yeng (Singapore Botanic Garden, 2006)
Three new species of Schismatoglottis - Schismatoglottis jelandii P.C.Boyce & S.Y. Wong, Schismatoglottis jepomii PC.Boyce & S.Y. Wong and Schismatoglottis maelii PC.Boyce S.Y. Wong - from Sarawak are described and included in the amendments to the key to Bornean Schismatoglottis published by Hay & Yuzammi (2000). All are illustrated.